Examining the underlying latent structure of the sports emotion questionnaire: Insights from the bifactor multidimensional item response theory - Hagan, John Elvis; Quansah, Frank; Ankomah, Francis; Agormedah, Edmond Kwesi; Srem-Sai, Medina; Schack, Thomas (Frontiers in Psychology, 2022)
Background: Despite the widespread use of the sports emotion questionnaire (SEQ) in several studies, it surprising that only few have explicitly tested the validity and utility of the instrument in non-western populations. Besides, the issue of dimensionality and the latent structure of the instrument remain inconclusive given that several authors have revealed different factor structure across diverse populations. The central concern is whether the items on the various dimensions, proposed for the original SEQ, offer adequate information to their respective expected subscale. This study purpose was to assess the underlying latent structure of the SEQ using confirmatory and bifactor MIRT models. Methods: Using a cross-sectional design, athletes from three West African countries, participating in the West African University Games were surveyed to respond to the SEQ. The data were analysed using first, a confirmatory factor analysis via the multidimensional item response (MIRT) model and second, with a bifactor MIRT analysis. Results: The results revealed that items on the SEQ instrument were fairly good in measuring the construct under the respective domains of the instrument. However, the outcome of the bifactor model showed that the majority of the items on the SEQ instrument explained common variance in relation to the general factor other than the specific domains (5-dimensions). Conclusion: Findings of the bifactor model question whether the sub-dimensions of the SEQ instrument are needed because there were traces of evidence showing that most of the items on the SEQ instrument were more discriminating proxies of the general factor than any of the five domains. It is concluded that instruments like SEQ should be scored for a general factor and not as sub-dimensions. Further investigations are encouraged by scholars within the area to probe the dimensionality of the SEQ.